The determination of factors that influence the noise pollution in Malaysia using fuzzy logic / Mohd Fazril Izhar Mohd Idris, Nur Afifah Zainol Abidin and Khairu Azlan Abd Aziz - Mohd Idris, Mohd Fazril Izhar; Zainol Abidin, Nur Afifah; Abd Aziz, Khairu Azlan (UiTM Cawangan Perlis, 2020)
Nowadays, the economy of our country has increased, so the use of transport, whether on land or by air, has also increased. This will lead to noise pollution, which will have an impact on human health. Noise pollution was an unpleasant sound that could have a negative impact on human health, such as sleep disturbance, hearing loss, annoyance, and stress. There are many factors that can cause noise pollution such as road traffic, aircraft, commercial construction, industrial and manufacturing noise. Therefore, the aim of this study is to determine the factor that influences noise pollution in Malaysia using Fuzzy Logic. The determination of factors that affect noise pollution in Malaysia using the Fuzzy Logic approach includes the determination of input and output variables, Fuzzification, Fuzzy Rule-Based, Fuzzy Inference Method and Defuzzification. In Defuzzification which is the last stage for Fuzzy logic, Centroid method used since it can give a result with more accurate and flexible. This study used road traffic noise, aircraft noise, industrial and manufacturing noise and commercial construction as factors for noise pollution, as well as input variables. This method was used to determine which factors have the most influence on noise pollution. The results of this study show that road traffic noise and industrial and manufacturing noise were factors which had an impact on noise pollution with a maximum value of 82. This shows that the aim of this study has been achieved.